Strengthening Village Statistical Literacy through Zero-Budget Collaboration: The Ga-Wat Desa Program in Buluran Kenali, Jambi - Titin Agustin Nengsih; Urwawuska Ladini; Betri Wendra; Della Amrina Yusra; Rini Warti; Vinny Yuliani Sundara; M. Yunus; Fadhlul Mubarak (LOSARI: Jurnal Pengabdian Kepada Masyarakat, 2026)
Low statistical literacy at the village and academic levels remains a major barrier to data-driven development planning in Indonesia. This community service program, Ga-Wat Desa (Village-Visiting Statistical Agents), aims to strengthen village-level statistical literacy and standardize toddler nutritional data governance through a zero-budget collaboration between UIN Sulthan Thaha Saifuddin Jambi’s Statistic Corner and BPS Jambi Province’s Desa Cantik program. Using a qualitative descriptive method, field observation, integrated training, and participatory data collection, three student statistical agents conducted field activities in Buluran, Kenali Urban Village, Jambi. Results show that the program, delivered by three student agents across 6 posyandu, standardized WHO anthropometric measurement practices for a target population of 88 toddlers, while providing valuable practicum experience for the student agents. The program operated entirely without a dedicated budget, relying solely on institutional commitment and resource sharing, demonstrating collaborative governance as a replicable model for public service transformation in Indonesian villages.